DAMPAK STUNTING TERHADAP PERKEMBANGAN KOGNITIF DAN PRESTASI BELAJAR ANAK SEKOLAH DASAR SERTA IMPLIKASINYA TERHADAP PROGRAM PENCEGAHAN - Anna Maria Oktaviani; Aliyah; Rafika Silfiyanty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stunting is a chronic nutritional problem that remains a major public health issue in Indonesia and poses serious long-term consequences for the quality of human resources. This condition results from prolonged inadequate nutritional intake, particularly during the first 1,000 days of life, leading to impaired physical growth and suboptimal brain development. The impact of stunting is not limited to short stature but also extends to delayed cognitive development, which directly affects academic achievement and learning capacity among elementary school children. This study aims to analyze the relationship between stunting, cognitive development, and academic achievement among elementary school students, as well as to examine its long-term implications for human resource quality. This research employs a quantitative approach with a cross-sectional design. The study sample was randomly selected from elementary school children living in areas with a high prevalence of stunting. Data collection involved anthropometric measurements to determine stunting status based on World Health Organization (WHO) standards, standardized cognitive tests to assess children’s cognitive abilities, and academic records and questionnaires to evaluate learning achievement. The collected data were analyzed using inferential statistical methods, including correlation and regression analyses, to identify the relationship and influence of stunting on cognitive development and academic achievement. The results are expected to indicate that stunted children demonstrate lower cognitive performance and poorer academic achievement compared to their non-stunted peers. These findings highlight the critical importance of comprehensive nutritional interventions and early stimulation, particularly during the first 1,000 days of life, as strategic efforts to prevent stunting and to improve educational outcomes and the overall quality of human resources in the future. Keywords: stunting, cognitive development, academic achievement, elementary school children.